Food consumption and assimilation of the adult dog conch Laevistrombus canarium (linnaeus 1758) at different temperatures - Wan Hassan, Wan Nurul Husna; S. M. Nurul Amin; Abd Ghaffar, Mazlan; Che Cob, Zaidi (Faculty of Science, University of Malaya, 2019)
Laevistrombus canarium (Linnaeus 1758) or the dog conch is a highly important fishery species with great potential for introduction into aquaculture. The present study evaluates food consumption and assimilation by the adult conch at different temperatures (i.e. 22°C, 26°C, 30°C and 34°C). The conchs were acclimated for one week in stocking tanks with well-aerated seawater of 30 PSU salinity and at ambient temperature of 26°C. Prior to experimentation, the gastric emptying level of the conchs were standardized by allowing them to feed till satiation, followed by 24 h starvation. Ten similar sized aquaria (20 x 15 x 15 cm) were used, each containing one individual conch. Each conch was provided with similar quantity of food (~ 102.13 ± 0.45 mg of sinking pellets) and they were allowed to feed within a 24 h period. The food consumption rate for adult conchs was significantly different (p<0.05) between different temperature regimes. Hence, the food absorption efficiency was also affected (p<0.05), which ranged from 55.21% to 74.75%. The food energy absorbed showed significant variations between temperatures (p<0.05). Higher food consumption and assimilation was recorded at 26°C followed by 30°C, 34°C and 22°C. Adult L. canarium can adapt well in captive conditions by efficiently digesting particularly food pellets. However, more studies are still needed, particularly by adopting longer exposure times as well as higher temperature ranges, in order to better understand the effect of temperatures on the species.